ANALISIS KUALITAS PELAYANAN DI MASA PANDEMI COVID-19 TERHADAP KEPUASAAN PENUMPANG DI BANDAR UDARA INTERNASIONAL SAM RATULANGI MANADO - Davi Rizki Krisnanda; Anton Budiarto; Laila Rochmawati (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
This study aims to analyze the quality of service in the Covid-19 pandemic on passenger satisfaction at Sam Ratulangi International Airport, Manado. And to see the queues at the check-in counters and the cleanliness of the toilets at Sam Ratulangi International Airport, Manado.The research method in this research is using quantitative descriptive research. The population in this study were all airline passengers operating at Sam Ratulangi International Airport, Manado. The sampling method in this study using quota sampling, which is a technique to determine a sample from a population that has certain characteristics used by researchers. Then the sample size used in this study were 55 respondents who were passengers operating at Sam Ratulangi Airport, Manado. The data analysis method used in this research is simple linear regression analysis with the help of the SPSS 26 program. The results of this study indicate that passenger satisfaction with facilities that are considered lacking in the eyes of passengers who are at Sam Ratulangi International Airport Manado with the lowest score of questionnaire results is the statement "Toilets and their equipment at Sam Ratulangi International Airport Manado are clean and not clean. smell” with a score of 108 or with a percentage of 39%.